Representasi Nilai Filosofis dan Sosiologis dalam Lelagon Lumbung Desa: Kajian Semiotika Roland Barthes - Teki Teguh Setiawan; Pitutur Tustho Gumawang; Wisnu Samodro (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Traditional artworks, amidst the tide of modernization and digitalization, face the challenge of being stigmatized as static relics of the past. However, in the midst of increasingly modern civilization, traditional artworks are perceived to possess philosophical values ​​for the younger generation. The meanings contained in traditional songs possess a social perspective lacking in most traditional songs composed in the modern era. The purpose of this article is to examine the lyrics of Ki Nartosabdo's song "Lumbung Desa" philosophically and sociologically, applying Roland Barthes's semiotic theory. The research method used is a qualitative descriptive approach to analyze semiotics, comprising the significance of denotation, connotation, and myth.The analysis shows that the denotation in the lyrics of "Lumbung Desa" depicts agricultural activities occurring in rural communities. Connotatively, the lyrics interpret the values ​​of human spirituality towards God, integrity in work, and food self-sufficiency. From a mythical perspective, the lyrics symbolize the values ​​of harmony in social life and mutual cooperation as a solid foundation for building national stability and progress. Further analysis of the song lyrics' relevance in the modern era shows that the meaning of "Lumbung" has transformed into financial and digital independence, while the value of "Rukun" points to the application of ethics in the use of digital media in the modern era. This article concludes that preserving traditional songs is a strategy to revive culture as a manifestation of material progress that impacts the well-being of modern society.